Moderating the role of Asset Growth and Firm Value on Governance Value and Economic Value Added Study: BUMN Companies Go Public on the Indonesia Stock Exchange - Masno Marjoah Marjohan (University of Merdeka Malang, 2023)
The purpose of the study was to determine and analyze the Green Governance and Corporate Social Responsibility effect on Company Value, moderating Corporate Governance Responsibility on Company Value in cement subsector manufacturing companies for the period 2013-2022. This research method is a cement subsector manufacturing SOE company that goes public on the Indonesia Stock Exchange, totaling 8 companies. Sample determination is used with purposive sampling method with Judgment Sampling approach with the number of samples observed as many as 8 companies. Data analysis in this study used MRA (moderated regression analysis). The results showed that company value has a significant positive effect on Green Governance and Corporate Social Responsibility, Green Governance has no significant effect on Company Value, Corporate Social Responsibility has a significant positive effect on Company Value, and Growth Opportunities can strengthen Green Governance in influencing Company Value and Growth Opportunity can moderate Corporate Governance Responsibility on BUMN Company Value in cement subsector manufacturing companies.